Distribution, virulence factors and antimicrobial resistance of Vibrio species isolated from cultured shrimp in Peninsular Malaysia - Wan Omar, Wan Haifa Haryani (2024)
Vibrio, the most common bacterium associated with crustacean diseases, poses a significant threat to shrimp farming due to outbreaks of vibriosis. Therefore, the study aims to provide a comprehensive database on the distribution of Vibrio spp. as well as virulence genes and antimicrobial resistance profiling in Malaysian shrimp farms. Briefly, a total of 210 cultured shrimp were collected from seven farms in Peninsular Malaysia. The findings revealed that 225 presumptive Vibrio isolates were isolated from cultured shrimp which were then subjected to biochemical test and molecular detection using pyrH gene analysis. Eventually, 13 different Vibrio spp. were successfully isolated and characterized including Vibrio parahaemolyticus (55%), V. communis (9%), V. campbellii (8%), V. owensii (7%), V. rotiferianus (5%), Vibrio spp. (4%), V. alginolyticus (3%), V. brasiliensis (2%), V. natriegens (2%), V. xuii (1%), V. harveyi (1%), V. hepatarius (0.4%) and P. damselae (3%). Based on virulence genes assessment, eight of the eleven virulence genes in this study were detected, including chiA (89%), flaC (74%), tlh (72%), toxR (70%), luxR (40%), pirA (11%), pirB (11%) and hlyA (0.4%). Other virulence genes, such as tdh, trh and ctxA, were not detected in any isolates (0%). From the virulence gene assessment, three Vibrio isolates were chosen for the pathogenicity test based on highest number present in each of the species. The isolates including V. parahaemolyticus S12-3, V. campbellii S10-4, and V. rotiferianus S24-4 were tested by immersion challenge test against postlarvae (PL) Penaeus monodon approximately PL-20 with three different concentrations of 1 × 106 CFU/mL, 1 × 107 CFU/mL, and 1 × 108 CFU/mL. The LC50 result revealed that the lowest were V. parahaemolyticus S12-3 (1 × 105 CFU/mL) followed by V. rotiferianus S24-4 (1 × 1011 CFU/mL) and V. campbellii S10-4 (1 × 1013 CFU/mL). Moreover, histopathological analysis showed sloughing of epithelial cells in hepatopancreatic tubule, haemocytic infiltration, massive vacuolation and loss of hepatopancreatic tubule structure. Meanwhile, the majority of the species tested were resistant to penicillin G (100%), but susceptible to norfloxacin (96%). According to the multiple antibiotic resistance (MAR) index, 84% of Vibrio spp. exhibited a MAR index value of more than 0.2. Thus, the findings suggested that a large number of Vibrio spp. were resistant to several antibiotics and had been exposed to antibiotics on a regular basis at the farms. Plasmid profiling revealed that 125 isolates from a total 225 of Vibrio isolates harboured plasmid with the size ranging from 1 kb and above 10 kb, separating the isolates into 23 plasmid profiles. After plasmid curing, Vibrio-positive plasmid was lost resistance to antibiotics. The findings revealed that the resistance to antibiotics in isolated Vibrio spp. were either chromosomal or plasmid mediated. In conclusion, ongoing monitoring of antibiotic-resistant microorganisms as well as understanding the genetic basis of resistance are essential to implement a strategy for minimizing AMR strain yet to improve shrimp farming management in Malaysia.